2010
DOI: 10.1111/j.1365-3164.2010.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic monolateral otomycosis in a dog caused by Aspergillus ochraceus

Abstract: Aspergillus ochraceus, a widely distributed filamentous fungus, was isolated and identified by cytology and culture as the cause of unilateral ceruminous purulent otitis in a 4-year-old male mixed-breed dog. The pathogenic role of the fungal isolate was confirmed by a good response to antifungal therapy and the absence of other pathogens. No underlying diseases were identified and the dog recovered after 3 weeks of therapy with oral itraconazole and topical miconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
10
0
2
Order By: Relevance
“…We have identified only 17 cases of Aspergillus otitis from a hospital population over a 25 year period. The majority of cases were unilateral, consistent with previously reported cases of Aspergillus otitis in dogs and humans . In humans bilateral otomycosis is more commonly seen in immunocompromised patients .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have identified only 17 cases of Aspergillus otitis from a hospital population over a 25 year period. The majority of cases were unilateral, consistent with previously reported cases of Aspergillus otitis in dogs and humans . In humans bilateral otomycosis is more commonly seen in immunocompromised patients .…”
Section: Discussionsupporting
confidence: 89%
“…Two case reports of dogs with Aspergillus otomycosis have been published describing treatment and outcome . To the best of the authors’ knowledge there are no studies that have evaluated Aspergillus otitis in a series of small animals.…”
Section: Introductionmentioning
confidence: 99%
“…Carpagnano et al often found A. ochraceus in exhaled breath condensate of lung cancer patients (27). In other mammals, it was associated with a case of otomycosis in a dog (45). Here, the three isolates were from different clinical origins (i.e., BAL fluid, ear, and heart valve).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus spp. y Curvularia spp,; sin embargo, se reconoce su importancia clínica en dermatomicosis, otomicosis y queratitis (3,(15)(16)(17).…”
Section: Introductionunclassified